Improving the Entrepreneurial Experience Through the Support Environment in the Ljubljana Urban Region – HR Support Environment for Entrepreneurship - Kovačević, Vanja; Marič, Miha (Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji, 2025)
Entrepreneurship is one of the key drivers of economic development, as it promotes job creation and strengthens the competitiveness of the economy. In the future, increasing emphasis will be placed on the development of innovative products and services across all economic sectors. Entrepreneurs, especially those at the beginning of their journey, face numerous challenges that impact their growth and long-term success. Providing appropriate support is crucial for enhancing competencies, encouraging innovation, and achieving stable and sustainable growth. Effective support improves the entrepreneurial experience and strengthens entrepreneurs’ ability to adapt to rapidly changing market conditions. The focus of the research is on examining the role of support mechanisms in fostering entrepreneurial development. In cooperation with the Regional Development Agency of the Ljubljana Urban Region (Sl. RRA LUR), we conducted a study based on a review of relevant literature, a survey of participants in support programs, and a structured interview with Dejan Marinčič, Advisor to the Director for Entrepreneurship and Innovation. By combining quantitative and qualitative research methods, we gained a comprehensive insight into the functioning of support programs and developed proposals to enhance existing support systems within the RRA LUR.